The Role of Stress Coping as a Moderator between Toxic Leadership and Turnover Intention in Millennial Workers - Yulianto, Cheryl Graciana; Fajrianthi; Samian (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
Currently, the turnover intention rate among millennial employees is high. Toxic leadership is one of the reasons for this high turnover intention rate. Toxic leadership can lead to a depletion of employee resources, encouraging them to leave the workplace. Based on the Conservation of Resources theory, this research aims to determine the role of coping stress as a moderator in the influence of toxic leadership on turnover intention. Participants consisted of 43 employees from PT X. The sampling technique used was purposive sampling. The instruments used were the toxic leadership scale, the Brief COPE, and the turnover intention scale. The results of the data analysis using the PROCESS MACRO by Hayes model 1 indicate that coping with stress does not moderate the influence of toxic leadership on Turnover Intention. This research is expected to provide information regarding the impact of toxic leadership on turnover intention, especially among millennial workers.